Analysis of User Requirements for an Educational Laboratory Material Inventory System Using the Quality Function Deployment (QFD) - Cipto Ramdhani Yusuf; Muhamad Sayuti; Annisa Indah Pratiwi; N. Neni Triana (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2026)
Inventory management in one of the educational laboratories in Karawang is still carried out manually, causing inconsistency in stock data with actual conditions, delays in updating information, and low efficiency in supporting practicum and research activities. This research aims to identify the needs of students and lecturers as the main users, then translate them into technical specifications for the development of laboratory inventory information systems. The method used is Quality Function Deployment (QFD) through House of Quality (Phase I) and Part Deployment (Phase II). Data was collected through observations, interviews, and questionnaires that have been tested for validity and reliability before being analyzed. The results of the study show four main needs of users, namely system access speed, data security, attractive interface, and ease of use. In QFD Phase I, these needs translate into priority technical characteristics in the form of servers and databases, menu structures, and interfaces and user experience. Furthermore, QFD Phase II produces eight priority component characteristics, including multi-device support, rapid system response, API integration with College Information Systems, responsive design, database management, simple navigation, data encryption, and high-availability servers. This research contributes through the application of QFD up to Phase II as a systematic approach in designing a laboratory inventory information system that is oriented to user needs so as to improve service quality, ease of use, and operational efficiency.